Paths out of poverty: Social entrepreneurship and sustainable development - Zhang, Xiaoyi; Sun, Yu; Gao, Yang; Dong, Yueqi (Frontiers in Psychology, 2022)
Poverty reduction in rural areas is an important development goal concerned by the international community, but the traditional poverty-reduction methods have certain drawbacks. Social entrepreneurship, with its innovative way to solve social problems, has gradually become a new sustainable development path to solve rural poverty. Using the case study method, this paper analyzes the social entrepreneurship process of 9 enterprises and the process mechanism of solving the rural poverty problem based on the identification and development of social opportunities. Our analysis suggests that social entrepreneurship is the process of identification, development and realization of social opportunities. Multidimensional rural poverty creates different social opportunities, including social opportunities in social, economic and ecological poverty. Enterprises integrate farmers into their value chain to develop and realize social opportunities, which is a sustainable means of poverty alleviation. In theory, we propose a conceptual framework for the sustainable development of social entrepreneurship and enriches the research on the process of realizing social opportunities in social entrepreneurship. In practice, we provide a sustainable development ideas for rural areas.